Impact of inflammatory diets on endocrine disorders in patients with diabetes mellitus (Research, Society and Development, 2020)
Introduction: Diabetes mellitus is a chronic non-communicable disease in which there are endocrine and metabolic disorders, such as oxidative stress and inflammatory processes due to hyperglycemia. These inflammatory processes have a multifactorial origin, including inadequate nutrition. In this sense, the objective of this review was to discuss the endocrine disorders of diabetes mellitus and its relationship with the dietary inflammatory index. Methodology: A narrative review was carried out based on the search for articles published in the Pubmed, Science Direct, SciELO and Cochrane Library databases, using the keywords “Diabetes Mellitus”, “Inflammation”, “Insulin Resistence”, “Oxidative Stress” and “Inflammatory Diet”. Result: Scientific studies suggest that some components of the diet cause oxidative stress and inflammation, which in turn affects the clinical picture of individuals with diabetes. It is possible to detect that diets based on the western lifestyle, with a diet rich in red meat, refined sugars, industrialized drinks and processed foods, are considered positive stimulators of the increase in the levels of inflammatory biomarkers, such as CRP, TNF-α and interleukins. Conclusion: there is a possible relationship between the presence of diabetes mellitus and a pro-inflammatory diet, requiring further studies on the topic addressed.